Radiofrequency ablation for liver tumors abutting complex blood vessel structures: treatment protocol optimization using response surface method and computer modeling - Zheng Fang; Hongjun Wei; Hanwei Zhang; Michael A. J. Moser; Wenjun Zhang; Zhiqin Qian; Bing Zhang (International Journal of Hyperthermia, 2022)
Objective To achieve a result of a large tumor ablation volume with minimal thermal damage to the surrounding blood vessels by designing a few clinically-adjustable operating parameters in radiofrequency ablation (RFA) for liver tumors abutting complex vascular structures.Methods Response surface method (RSM) was employed to correlate the ablated tumor volume ([Formula: see text]) and thermal damage to blood vessels ([Formula: see text]) based on RFA operating parameters: ablation time, electrode position, and insertion angle. A coupled electric-thermal-fluid RFA computer model was created as the testbed for RSM to simulate RFA process. Then, an optimal RFA protocol for the two conflicting goals, namely (1) large tumor ablation and (2) small thermal damage to the surrounding blood vessels, has been achieved under a specific ablation environment.Results Linear regression analysis confirmed that the RFA protocol significantly affected [Formula: see text] and [Formula: see text] (the adjusted coefficient of determination [Formula: see text] = 93.61% and 95.03%, respectively). For a proposed liver tumor scenario (liver tumor with a dimension of 4[Formula: see text]3[Formula: see text]2.9 cm3 abutting a complex vascular structure), an optimized RFA protocol was found based on the regression results in RSM. Compared with a reference RFA protocol, in which the electrode was centered in the tumor with a 12-min ablation time, the optimized RFA protocol has increased [Formula: see text] from 98.1% to 99.6% and decreased [Formula: see text] from 4.1% to 0.4%, achieving nearly the complete ablation of proposed liver tumor and ignorable thermal damages to vessels.Conclusion This work showed that it is possible to design a few clinically-adjustable operating parameters of RFA for achieving a large tumor ablation volume while minimizing thermal damage to the surrounding blood vessels.